All Days 1989
DOI: 10.2118/19090-ms
|View full text |Cite
|
Sign up to set email alerts
|

Production and Stimulation Analysis of Multiple Hydraulic Fracturing of a 2,000-ft Horizontal Well

Abstract: The performance of multiple hydraulic fracturing treatments along a 2000-foot horizontal well bore was completed in a gas bearing, naturally-fractured shale gas reservoir in Wayne County, West Virginia. Pre-frac flow and pressure data, hydraulic fracturing treatments, and post-stimulation flow and pressure data form the basis from which a comprehensive analysis was performed. Average field production from 72 wells was used as baseline data for the analysis. Such data was used to show the significance of enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Hydraulic fracturing has been shown to be an effective way of significantly enhancing the performance of horizontal wells (1). It is especially beneficial in low permeability formations, and where low vertical permeability reduces the effectiveness of horizontal wells.…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic fracturing has been shown to be an effective way of significantly enhancing the performance of horizontal wells (1). It is especially beneficial in low permeability formations, and where low vertical permeability reduces the effectiveness of horizontal wells.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple fracturing of horizontal wells has been shown to be both a viable and successful approach. In a tight naturally fractured gas reservoir, the productivity of a multi-fractured horizontal well is shown to be several times greater than that achieved by a stimulated vertical well (Yost A.B., 1989 (Horne., 1995). The study showed that the effectiveness of creating multiple fractures along a horizontal well depends on the relative lengths of the well and the fractures as well as the time at which the comparison is economically significant.…”
Section: Hydraulic Fracturing In Horizontal Wellsmentioning
confidence: 99%
“…The significance of enhanced production from a horizontal well in a field that was partially depleted was studied [Yost and Overbey, 1989]. The performance of multiple hydraulic fracturing treatments along a horizontal well was evaluated.…”
Section: Devonian Shalementioning
confidence: 99%